Efficacy and safety of rimegepant 75 mg orally disintegrating tablet for the acute treatment of chronic rhinosinusitis in adults: Results from a multicenter, randomized, placebo-controlled, phase 2/3 trial - Daniel Franjic; Robert J. Fountaine; Catherine Nalpas; Budhaditya Goswami; Terence Fullerton (PLoS ONE, 2026)
Calcitonin gene-related peptide (CGRP) activation could play a causal role in the pathophysiology of chronic rhinosinusitis (CRS), a long-term inflammatory disease of the nasal cavity and paranasal sinuses. This study investigated the efficacy and safety of rimegepant 75 mg orally disintegrating tablet, a CGRP receptor antagonist, versus placebo for acute treatment of CRS. This double-blind, randomized, placebo-controlled, phase 2/3 trial enrolled adults with CRS in the United States. Participants were randomized 1:1 to rimegepant or placebo stratified by the presence or absence of nasal polyps. Participants were dispensed a single dose of study drug administered when they experienced a qualifying facial pain/pressure/fullness (Numeric Rating Scale [NRS] ≥6). The primary efficacy endpoint was a change from baseline [CFB] at 2 hours post dose in the intensity of facial pain/pressure/fullness) with baseline NRS score ≥6. Secondary endpoints included a CFB at 2 hours post dose in the NRS score for nasal obstruction/congestion and nasal discharge, and Total Nasal Symptom Score (TNSS); proportion of participants reporting headache pain relief at 2 hours post dose; and proportion of participants using rescue medication within 24 hours post dose. Efficacy outcomes were evaluated using a linear model. Of 261 participants (mean age: 49.3 years) randomized to rimegepant (n = 131) or placebo (n = 130), 96 and 100 had evaluable data for efficacy analyses. No significant treatment differences (P > 0.05) were observed between groups for the primary (CFB at 2 hours post dose in the NRS score for intensity of facial pain/pressure/fullness, least-squares mean difference [95% CI] −0.1 [−0.7, 0.5]) and secondary outcomes. There were no serious safety findings. To our knowledge, this study is the first to explore the use of CGRP receptor antagonists for CRS. Although no treatment differences were identified, the findings could contribute to the design of future clinical trials and better disease understanding. Trial registration ClinicalTrials.gov NCT05248997 .